2019
DOI: 10.1158/0008-5472.can-18-1754
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of SHISA3 Promotes Nasopharyngeal Carcinoma Metastasis by Reducing SGSM1 Stability

Abstract: Altered DNA methylation is a key feature of cancer, and aberrant methylation is important in nasopharyngeal carcinoma (NPC) development. However, the methylation mechanisms underlying metastasis of NPC remain unclear. Analyzing data from public databases and conducting our own experiments, we report here that promoter hypermethylation of SHISA3 is common and contributes to the downregulation of this gene in many types of tumors, including NPC. SHISA3 suppressed NPC cell invasion and metastasis in vitro and in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Methylation modification plays an important role in NPC metastasis, but the mechanisms remain poorly understood. We have previously reported that hypermethylation of the HOPX, RAB37, and SHISA3 genes might serve as molecular biomarkers to predict NPC metastasis [17,26,27]. Therefore, the mechanisms and significance of methylation regulation in NPC are worthy to be study in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation modification plays an important role in NPC metastasis, but the mechanisms remain poorly understood. We have previously reported that hypermethylation of the HOPX, RAB37, and SHISA3 genes might serve as molecular biomarkers to predict NPC metastasis [17,26,27]. Therefore, the mechanisms and significance of methylation regulation in NPC are worthy to be study in greater detail.…”
Section: Discussionmentioning
confidence: 99%
“…When SHISA3 is silenced, the increased SGSM1 polyubiquitylation and degradation abrogates one of the brakes impinging on the MAPK pathway. Accordingly, SHISA3 is downregulated in various tumor types, including nasopharyngeal carcinoma (NPC) in which the SHISA3 promoter hypermethylation correlates with the SHISA3 ability to suppress the NPC in vitro invasion and in vivo lymph node metastasis [96].…”
Section: Dna Methylation In Emt and Metastasis Mechanismsmentioning
confidence: 99%
“…Total RNA was extracted using TRIzol regent (Life Technology, Carlsbad, USA) and converted to cDNA using a M-MLV reverse transcriptase kit (Promega). Quantitative PCR was performed and analyzed as described previously [41]. The primer sequences are shown in Supplementary Table 2.…”
Section: Rna Isolation and Quantitative Pcrmentioning
confidence: 99%